A socio-demographic study on seroprevalence of SARS-CoV-2 antibodies and associated factors in a rural population in Andhra Pradesh - Chirathapudi, Jaya Sandhya; Karampudi, Amulya Sanghamithra; Aijaz, Ayesha; Naidana, Partha Sarathy (International Journal Of Community Medicine And Public Health, 2023)
Background: SARS-CoV-2 is an enveloped, single stranded RNA beta corona virus that belongs to the family Coronaviridae. The S and N proteins are the principal immunogens used for the detection of anti – SARS-CoV-2 specific antibodies.2 The first subunit (S1) mediates the attachment of the virus to human cells via its receptor - binding domain (RBD), and the second one (S2) mediates membrane fusion for viral entry. Antibodies that bind to the S protein can neutralize corona viruses. Methods: It was a community based analytical cross-sectional study done in rural areas of Eluru district, A.P. State. From each village 30 members were selected by using systematic random sampling. A sample of 120 was included. Blood samples from the selected individuals were taken Humoral responses (Ig G) were assessed using an ICMR approved Micro well ELISA test for the semi-quantitative detection of COVID 19 (SARS-CoV-2) neutralizing antibodies in Human serum samples. Results: In the present study 46 (28.3%) had higher education, 15 (12.5 %) belong to farmers, 84 (70%) of them belong to Hindus, 94 (78.3%) of them belong to nuclear family. History of COVID 19 (p=0.02), period from recent dose of covid vaccination (p=0.04) were found to be statistically significant. Conclusions: High seroprevalence in this study suggests that COVID-19 vaccination remains the best method to control the COVID-19 pandemic. It is necessary to encourage the public to take vaccination.